Health Promotion Initiatives for Reintegrating Employees with Depressive Disorder into the Workplace - Egba, A. N, Egba, A. N; Omaka-Amari, L. N (NIGERIAN JOURNAL OF HEALTH PROMOTION, 2016)
This paper looked at health promotion initiatives for reintegrating employees with depressive disorder into the workplace. The paper saw depression as a severe mood disorder characterized by abnormal behaviours that interfere with an individual’s normal daily living. Health promotion initiatives necessary for the reintegration of depressed employees to work were identified and discussed. Health promotion in this context was conceived as the combined efforts of employers, employees and society to improve the health and wellbeing of people at work. The paper noted that the essence of these health promotion initiatives is to create a workplace that provides workers with a mentally healthy and supportive environment while returning to work. Such initiatives discussed in the paper were supportive work, health education, health screening, quality circle, holistic approach, communication, incentive, special and multi-modular methodology initiatives. Thereafter, the paper concluded that health promotion initiatives for reintegrating employees with depressive disorder into the workplace is important for the employees, their families, employers and the society, through preventing the possibility of such employee of becoming a nuisance to the world in general. Therefore, it was recommended among others that health promotion in the workplace should be a top priority of the government and employers since one’s health determines his/her ability to work effectively in any organization.